Minimum Investment Requirements, Financial Market Globalization, and Symmetry Breaking - ZHANG, Haiping (Institutional Knowledge at Singapore Management University, 2014)
We incorporate wealth heterogeneity and the minimum investment requirements in the model of Matsuyama (2004, Econometrica) and provide a complete characterization of symmetry breaking. In particular, we identify the extensive margin of investment as a key channel through which the interest rate may respond positively to capital accumulation, or equivalently, the interest rate can be higher in the rich than in the poor countries. Then, ﬁnancial market globalization may lead to “uphill” capital ﬂows from the poor to the rich countries, which widens the initial cross-country income gap and leads to income divergence among inherently identical countries, a phenomenon that Matsuyama calls symmetry breaking.